1992
DOI: 10.1093/jmedent/29.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluation of Five Repellents Against the Black Flies Prosimulium mixtum and P. fuscum (Diptera: Simuliidae)

Abstract: Deet (N,N-diethyl-3-methyl-benzamide), the lactone CIC-4 ([2-hydroxy-methyl-cyclohexyl] acetic acid lactone), the USDA Proprietary Chemicals AI3-37220 (1- [3-cyclohexen-1-ylcarbonyl]-2-methylpiperidine) and ++[3-35765 (1-[3-cyclohexen-1-ylcarbonyl] piperidine), and the U.S. military extended duration repellent formulation (EDRF) of deet were evaluated for repellency in the laboratory and field against the black flies Prosimulium mixtum and P. fuscum. CIC-4, AI3-37220, and AI3-35765 were as effective as deet at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…AI3Ð37220 (220) contains two asymmetric centers and achiral synthesis yields a racemic mixture of 1S,2ЈR, 1R,2'S, 1R,2ЈR, and 1S,2'S stereoisomers. The racemic mixture proved to be an effective repellent against a variety of blood-feeding arthropods (Robert et al 1992, Coleman et al 1993, Walker et al 1996, Frances et al 1996, Frances et al 1998 This article reports the results of research only. Mention of a proprietary product does not constitute an endorsement or a recommendation by the USDA or the Department of Defense for its use.…”
mentioning
confidence: 99%
“…AI3Ð37220 (220) contains two asymmetric centers and achiral synthesis yields a racemic mixture of 1S,2ЈR, 1R,2'S, 1R,2ЈR, and 1S,2'S stereoisomers. The racemic mixture proved to be an effective repellent against a variety of blood-feeding arthropods (Robert et al 1992, Coleman et al 1993, Walker et al 1996, Frances et al 1996, Frances et al 1998 This article reports the results of research only. Mention of a proprietary product does not constitute an endorsement or a recommendation by the USDA or the Department of Defense for its use.…”
mentioning
confidence: 99%
“…In IPM programs related to animal and human health, DEET and other synthetic repellents have been used extensively against mosquitoes [274][275][276][277][278][279][280][281][282][283][284][285][286], against blackflies [287], and against ticks [288]. Recently, the use of natural products as insect repellents has had renewed interest as well.…”
Section: Containment and Concentration This Technique Also Relies Onmentioning
confidence: 99%
“…Robert et al (1992) found 220 and 765 were more effective than deet in laboratory and Þeld evaluations against black ßies. Initial sensitivity tests of these piperidine compounds and deet against Anopheline mosquitoes and Phlebotomine sand ßies (Coleman et al 1993) showed that 220 and 765 were as effective as deet.…”
mentioning
confidence: 95%